Effects of quarry blasting towards the residential area at Kangkar Pulai, Johor, Malaysia - Karthigeyan a/l AL. Ramanathan; Rini Asnida Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2019)
The drill and blast technique have been widely used recently due to demand for natural building materials like rock aggregates. However, the intensity of blasting effects has been questioned on its validity towards the nearby residential areas. In this study, the blasting effects from Quarry A and B has been assessed based on constant location of the residential areas (Taman Pulai Hijauan and Taman Bandar Baru Kangkar Pulai, respectively) using the empirical formulations only. The blasting effects are highly dependent on the maximum instantaneous charge in blast holes (Q) which are dependent on parameters like number of blast holes, charge per column, Powder Factor and number of blast per delay. This study was able to show that with an increase of the independent variables, the Q value rises significantly. The average Q value from Quarry A (181.07 kg) was slightly higher than Quarry B (180.22 kg). The correlations made for each quarry showed that Quarry A had a better regression line with lower standard error due to the high number of blast data obtained during the monitoring period of about 1 year and 8 months. Meanwhile, the impact assessments showed higher PPV (Peak Particle Velocity) value at higher Q holding blast holes in Quarry A compared to Quarry B and decreases with increasing distance. The similar relationship was observed for the air blast assessments. Yet, all of the blasts produced are relatively within safe limits which are less than 5 mm/s Mineral & Geosciences Department (JMG) and less than 125 dBL United States Bureau of Mining (USBM). Thus, extra precaution can be taken by estimating the suitable Q value such as A (97.66 kg) and B (271.68 to 495.01 kg) to maintain safe blasting operations and prevent damages to the nearby residential areas.